Os desafios do trabalho digno: diálogos com o sistema de justiça e histórias de vida dos catadores de materiais recicláveis de Vitória/ES - Pinheiro, Priscila Tinelli (2018)
The present thesis analyzes the possible approximations between institutions of the justice system and recyclable waste workers with a view to improve the harvesting activity and attain decent work. The “Sociology of Absences” of Boaventura de Sousa Santos (2010) was adopted as methodology and basic theory, based on the valorization of the experiences produced in the present time. Accompanied by techniques as life history research with the current presidents of associations of collectors of recyclable materials located in the city of Vitória/ES and semi-structured interviews with the representatives of the Public Prosecutor's Office and the Public Defender's Office of the State of Espírito Santo. The objective was to understand the experiences of these subjects through the rescue of their memories and, with that, to delineate the labor identity of these workers at the same time in which were extracted their understandings about decent work. The parameters established by Gabriela Neves Delgado (2006) were used for the analysis of variables in this theoretical category, based on respect for the physical and moral integrity of the work coupled with the right to pecuniary consideration. The main results are the formation of a subalternized labor identity resulting from repeated invisibility situations present in the life trajectory of the collectors participating in the research. This situation is aggravated by the absence of public actions and the distancing of the public agents surveyed with those social actors, which acts as a barrier preventing the establishment of an effective network and dialogue that involves the associations of collectors of recyclable materials and the Brazilian justice system with a view to creating spaces that make it possible to go beyond the harvesting activity.